The effectiveness of olfactory training for chronic olfactory disorder following COVID-19: a systematic review - Treder-Rochna, Natalia; Mańkowska, Aleksandra; Kujawa, Wiktoria; Harciarek, Michał (Frontiers in Human Neuroscience, 2024)
Background: Chronic olfactory disorders are some of the most frequent post-COVID-19 presentations. Olfactory training (OT) is currently the most popular method used for treating post-viral olfactory dysfunction (PVOD). We evaluated the effect of olfactory training on the chronic olfactory disorders of patients infected with COVID-19.Methodology: A systematic literature search was performed as per PRISMA guidelines in PubMed, Scopus, Web of Science, EBSCOhost, and the Cochrane Library. Only patients with chronic olfactory disorders of 30 days or more were included. The primary outcome was the olfactory score at the end of follow-up.Results: Fourteen studies (1596 participants) were included in this review. Among the included studies, up to 10 were RCTs. Nine studies assessed the combined effects of adjuvant therapy and olfactory training, while five studies assessed only OT.In our assessment, olfactory training alone produces significant improvements in chronic olfactory dysfunctions. However, a combined therapy approach is essential to achieve more effective outcomes. Integrating olfactory training with adjuvants like CoUltraPEALut, Cerebrolysin, and oral Vitamin A has demonstrated substantial benefits in enhancing post-COVID-19 olfactory function. Strict adherence to the OT protocol and extending the duration of OT to three months or more significantly enhance treatment outcomes.